MEDICAL EMERGENCIES PREPAREDNESS IN DENTAL CLINIC AMONG POSTGRADUATE RESIDENTS IN NEPAL - Bhagat, Tarakant; Shrestha, Ashish; Kumari Agrawal, Santosh; Gautam, Ujwal; Mishal, Ratna (Journal of Chitwan Medical College, 2024)
Background: Serious medical emergencies in dental practices are generally rare (one in 3-5 years) but if it happens it is life threatening to the patient. Adequate knowledge and competency, training of the dental practitioners is necessary to avoid such life-threatening conditions. The study was conducted to assess the preparedness of medical emergencies among postgraduate dental students of Nepal. Methods: An online questionnaire based cross-sectional study was conducted among all post graduate dental students from all the dental colleges of Nepal. Pretested, validated, close ended questionnaire was used. Questionnaire consisted of twenty medical emergency situations and five questions regarding self-evaluation of training regarding the management of medical emergencies. Chi-square test was used to assess association between competency in managing medical emergency situations and years of academic experience during post-graduation. P- value <0.05 was considered statistically significant. Results: More than 70% participants answered correct management of medical emergency situations. Almost 20% disagreed and 20% don’t know about the management of such situations. Only 28% received training in the management of medical emergencies during undergraduate dental program. More than 50% were moderately satisfied with their knowledge about medical emergencies. Conclusions: The results of the study showed that knowledge to handle commonly occurring medical emergencies was higher. Most of the participants did not attend any training regarding medical emergencies. And those who attended felt there is need for further training in the management of emergency medical cases in the dental chair.